Saudi Identity In 2030 Vision From The Perspective Of Arts And Crafts Of Saudi Society (Journal of Namibian Studies : History Politics Culture, 2024)
Saudi Arabia’s Islamic heritage and cultures had a big impact on the country's craft sector. To preserve its historical treasure, the government has put forth the 2030 vision, which aims to revitalize and reintroduce local crafts and arts in accordance with its values and traditions. Handicrafts contribute to the monetary development and help in adding more job opportunities and increasing income for a large number of families, in addition to maintaining the social roots and character of the country. They also attract tourists who like to collect handmade articulations made from different materials. Handicrafts are considered part of Saudi Arabia's significant features that should be revived to lead the community to success and growth. Handicrafts as a part of the Saudi heritage represent the identity of the community which mixes the present and the future with the past. The government of Saudi Arabia according to its vision 2030 is aiming to revive the heritage of cultural crafts to restore the country's identity through building a craft center within the scope of local historic sites. The government developed the National Project of Profession Heritage Management to authenticate traditional professions and handicrafts.